2021
DOI: 10.1111/jocd.14612
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 38 serum level is increased in patients with vitiligo, correlated with disease severity, and associated with signs of disease activity

Abstract: Background Vitiligo is an acquired cutaneous depigmenting disease caused by a T helper (Th) 1–cytotoxic T cells driven autoimmune attack against melanocytes, in which Th17 is also involved. Interleukin (IL)‐38 belongs to the IL‐1 family of cytokines and suppresses Th1 and Th17 activation. IL‐38 protein and mRNA levels have been found to be elevated in various autoimmune disorders and correlated with disease severity and activity, including psoriasis, systemic sclerosis, rheumatoid arthritis, and atopic dermati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
2
3
2
Order By: Relevance
“…BMI shows a trend towards higher BMI corresponding with lower IL-38 concentrations ( Figure 3D ), as was observed before ( 28 ). Also, age shows an inverse correlation with IL-38 concentrations ( Figure 3E ), which also corresponds with previously published data ( 28 , 43 ). Lastly, we determined whether IL-38 remains stable over time in two cohorts for which multiple consecutive samples were available.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…BMI shows a trend towards higher BMI corresponding with lower IL-38 concentrations ( Figure 3D ), as was observed before ( 28 ). Also, age shows an inverse correlation with IL-38 concentrations ( Figure 3E ), which also corresponds with previously published data ( 28 , 43 ). Lastly, we determined whether IL-38 remains stable over time in two cohorts for which multiple consecutive samples were available.…”
Section: Resultssupporting
confidence: 92%
“…Age showed a negative correlation with IL-38 concentrations, and in BMI a (although not significant) negative trend was observed. These observations were also comparable with prior studies ( 28 , 41 , 43 ). Lastly, no major variation over longer time courses was observed, which had also been shown before in 48 subjects over a time period of a year ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, an association of IL-38 rs7570267 and rs3811058 single nucleotide polymorphism with RA susceptibility has been shown [ 18 ]. In another study on RA patients, elevated levels of IL-38 was reported in plasma of patients compared to healthy controls [ 28 ]. Rudloff et al measured the IL-38 serum level in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%